2017
DOI: 10.1590/1806-9282.63.04.324
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral polyneuropathy in severely obese patients with metabolic syndrome but without diabetes: Association with low HDL-cholesterol

Abstract: Conclusion:In non-diabetic Ob-II,III,MetS patients, PPN defined by the MNSI showed a high prevalence and was associated with low levels of HDL-cholesterol. In order to diagnose that complication, neurological evaluation should be performed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Taken together, our results provide strong evidence that the disruption of nerve mitochondrial/ myelin lipid homeostasis observed in obese (pre)diabetic mice is not causally linked to hyperglycemia, dysinsulinemia, or insulin resistance but rather seems to be primarily driven by other components of the metabolic syndrome, namely obesity and/or hyperlipidemia. Consistent with this notion, a high prevalence of peripheral neuropathy has been reported in severely obese nondiabetic patients (49)(50)(51)(52). Moreover, an excess of dietary saturated fatty acids has been shown to be sufficient to drive peripheral nerve damage by impairing mitochondrial function and motility in dorsal root ganglion neurons (53,54).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Taken together, our results provide strong evidence that the disruption of nerve mitochondrial/ myelin lipid homeostasis observed in obese (pre)diabetic mice is not causally linked to hyperglycemia, dysinsulinemia, or insulin resistance but rather seems to be primarily driven by other components of the metabolic syndrome, namely obesity and/or hyperlipidemia. Consistent with this notion, a high prevalence of peripheral neuropathy has been reported in severely obese nondiabetic patients (49)(50)(51)(52). Moreover, an excess of dietary saturated fatty acids has been shown to be sufficient to drive peripheral nerve damage by impairing mitochondrial function and motility in dorsal root ganglion neurons (53,54).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, fatty acid transport has been proposed to regulate cardiolipin biosynthesis (56). Finally, clinical studies have concluded that obesity and hyperlipidemia are strongly associated with diabetic neuropathy (50,57,58), even under nondiabetic conditions (49,59), while epidemiological and preclinical studies on the etiology of peripheral neuropathies have proposed hyperlipidemia as a novel risk/causal factor (12-16, 60-62).…”
Section: Discussionmentioning
confidence: 99%
“…The mean TGL in the DPN group was 146.95 mg/dl, compared to 130.45 mg/dl in the control group. People with DPN were found to have a higher prevalence of hypertriglyceridemia [14][15][16] . The average total cholesterol levels of individuals with DPN and those without DPN were 217.4 mg/dl, and Katulanda et al also discovered no statistically significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%